Efektivitas stimulasi fisik terhadap reflek hisap neonatal hyperbilirubinemia di bawah fototerapi: A literature review - Veronika, Ika Bayu Septi; Nani, Desiyani (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Hyperbilirubinemia is the level of bilirubin in the blood and body tissues of infants that exceeds the normal limit. This condition is not dangerous, but prevention, detection and management of hyperbilirubinemia in newborns remains a priority to reduce the neurotoxic effects of bilirubin, both short and long term including the possibility of severe hyperbilirubinemia. To determine the fulfillment of fluid needs in neonates, hyperbilirubinemia is related to the sucking reflex in the neonate itself. Purpose: To determine the effectiveness of physical stimulation on the sucking reflex in neonates with hypobilirubinemia undergoing phototherapy. Method: Literature review research sourced from national and international journals with a search strategy using the Google Scholar, BMC, Sage Journal, and ScienceDirect databases published in the last 10 years. Results: Non-invasive physical therapy stimulation has many benefits and does not require special equipment in its implementation. This stimulation is effective in increasing the sucking reflex in hyperbilirubinous neonates undergoing phototherapy which is characterized by a decrease in bilirubin levels. Conclusion: Physical stimulation can increase the sucking reflex in hyperbilirubinous neonates undergoing phototherapy. Keywords: Hyperbilirubinemia Neonatal; Physical Stimulation; Sucking Reflex. Pendahuluan: Hiperbilirubinemia merupakan kadar bilirubin dalam darah dan jaringan tubuh bayi yang melebihi batas normal. Kondisi ini tidak berbahaya, namun upaya pencegahan dan deteksi serta penatalaksanaan hiperbilirubinemia pada bayi baru lahir tetap menjadi prioritas untuk mengurangi efek neurotoksik bilirubin, baik jangka pendek maupun jangka panjang termasuk kemungkinan hiperbilirubinemia berat. Memastikan terpenuhinya kebutuhan cairan pada neonatus, hiperbilirubinemia berkaitan dengan refleks hisap pada neonatus itu sendiri. Tujuan: Untuk mengetahui efektivitas stimulasi fisik terhadap refleks menghisap pada neonatus dengan hipobilirubinemia yang menjalani fototerapi. Metode: Penelitian tinjauan literatur yang bersumber pada jurnal nasional maupun internasional dengan strategi pencarian menggunakan database Google scholar, BMC, Sage Journal, dan ScienceDirect terbitan 10 tahun terakhir. Hasil: Stimulasi fisik terapi non-invasif memiliki banyak manfaat dan tidak memerlukan peralatan khusus dalam pelaksanaannya. Stimulasi tersebut efektif meningkatkan refleks menghisap pada neonatus hiperbilirubinosa yang menjalani fototerapi yang ditandai dengan penurunan kadar bilirubin. Simpulan: Stimulasi fisik dapat meningkatkan refleks menghisap pada neonatus hiperbilirubinosa yang menjalani fototerapi. Kata Kunci: Hiperbilirubinemia Neonatal; Stimulasi Fisik; Refleks Hisap.